Accuracy of pedicle screw placement based on preoperative computed tomography versus intraoperative data set acquisition for spinal navigation system - Hao Liu; Weikai Chen; Tao Liu; Bin Meng; Huilin Yang (Journal of Orthopaedic Surgery, 2017)
Aim: To investigate the accuracy of pedicle screw placement based on preoperative computed tomography in comparison with intraoperative data set acquisition for spinal navigation system. Methods: The PubMed (MEDLINE), EMBASE, and Web of Science were systematically searched for the literature published up to September 2015. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines. Statistical analysis was performed using the Review Manager 5.3. The dichotomous data for the pedicle violation rate was summarized using relative risk (RR) and 95% confidence intervals (CIs) with the fixed-effects model. The level of significance was set at p < 0.05. Results: For this meta-analysis, seven studies used a total of 579 patients and 2981 screws. The results revealed that the accuracy of intraoperative data set acquisition method is significantly higher than preoperative one using 2 mm grading criteria (RR: 1.82, 95% CI: 1.09, 3.04, I 2 = 0%, p = 0.02). However, there was no significant difference between two kinds of methods at the 0 mm grading criteria (RR: 1.13, 95% CI: 0.88, 1.46, I 2 = 17%, p = 0.34). Using the 2-mm grading criteria, there was a higher accuracy of pedicle screw insertion in O-arm-assisted navigation than CT-based navigation method (RR: 1.96, 95% CI: 1.05, 3.64, I 2 = 0%, p = 0.03). The accuracy between CT-based navigation and two-dimensional-based navigation showed no significant difference (RR: 1.02, 95% CI: 0.35-3.03, I 2 = 0%, p = 0.97). Conclusions: The intraoperative data set acquisition method may decrease the incidence of perforated screws over 2 mm but not increase the number of screws fully contained within the pedicle compared to preoperative CT-based navigation system. A significantly higher accuracy of intraoperative (O-arm) than preoperative CT-based navigation was revealed using 2 mm grading criteria.